Tannins - Structural Properties, Biological Properties and Current Knowledge 2020
DOI: 10.5772/intechopen.86420
|View full text |Cite
|
Sign up to set email alerts
|

Food Ellagitannins: Structure, Metabolomic Fate, and Biological Properties

Abstract: Food sources of ellagitannins (ETs) are numerous, and dietary intake of these compounds is estimated up to 12 mg/day in some countries, even though ETs have been considered in the past as not bioavailable like other tannins and were mostly neglected by nutritionists. Nonetheless, new insights show that ETs are bioconverted by microbiota in the gut into metabolites called urolithins, which are bioavailable and can reach relatively high physiological concentration in the body up to 7 days after ingestion. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…In our study, punicalagin, pedunculagin, valoneic acid dilactone, HHDPG, and ellagic acid are the ellagitannins detected, whereas cyanidin-3- O -glucoside and delphinidin-3- O -glucoside were the major anthocyanins. Ellagitannins are metabolized to ellagic acid and then to urolithin compounds, which are considered responsible for the biological activities of ellagitannins ( Villalba et al, 2019 ). Punicalagin demonstrated a cardioprotective effect in diabetic conditions where it significantly decreased elevated cTn-1 to normal levels, attenuated IL-1b, IL-6, and TNF-α, and ameliorated the lipid profile in a streptozotocin-induced diabetic model ( El-Missiry et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, punicalagin, pedunculagin, valoneic acid dilactone, HHDPG, and ellagic acid are the ellagitannins detected, whereas cyanidin-3- O -glucoside and delphinidin-3- O -glucoside were the major anthocyanins. Ellagitannins are metabolized to ellagic acid and then to urolithin compounds, which are considered responsible for the biological activities of ellagitannins ( Villalba et al, 2019 ). Punicalagin demonstrated a cardioprotective effect in diabetic conditions where it significantly decreased elevated cTn-1 to normal levels, attenuated IL-1b, IL-6, and TNF-α, and ameliorated the lipid profile in a streptozotocin-induced diabetic model ( El-Missiry et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than 1000 ETs have been detected to occur in many plants; nevertheless, few of them are fit for human consumption. Fruits including strawberries, berries, pomegranate, and nuts and seeds are rich in edible ETs, within which raspberries and cloudberries are the most abundant sources, as are processed foods, including fruit-derived beverages, jams and cakes (Table 1) [1,3,17]. In general, fruits of the genus Rubus are the most studied for their content in ETs and EA.…”
Section: Ellagitannins and Ellagic Acid 21 Natural Sources And Occurr...mentioning
confidence: 99%
“…Therefore, obviously, the rational use of these by-products may lead the pharmaceutical, nutraceutical and cosmetic industries to the development of valuable products for human health. Furthermore, many scientific papers discuss various plant species for their significant amount in ETs and EA [1][2][3]17]. Plant families, such as Myrtaceae, Rosaceae, Asteraceae and Fagaceae, are reported to include several plant genera, which produce ETs and EA [33,34].…”
Section: Ellagitannins and Ellagic Acid 21 Natural Sources And Occurr...mentioning
confidence: 99%
“…Studies have shown that urolithins are much more readily bioavailable and appear in human systemic circulation within a few hours of pomegranate ingestion reaching maximum concentrations between 24 and 48 hours. They were found to exist in both free and conjugated forms in the plasma and urine [ 8 , 9 ]. In view of this they are considered the bioactive forms of ETs.…”
Section: Reviewmentioning
confidence: 99%